Pansclerotic morphea: A case report - Sadia, Anum; Sadia, Anum (Journal of Pakistan Association of Dermatologists, 2022)
Generalized disabling pansclerotic morphea is a rare and mutilating form of morphea involving the dermis, subcutaneous tissue, fat, muscle, and even bone. It most often occurs in young children but adults can also be affected. We report a case of rapidly progressing and disabling adult onset generalized pansclerotic morphea, which responded well to methotrexate and steroid pulse therapy. Â